Ultrafast isomerization in acetylene dication after carbon K-shell ionization - Zheng Li (Nature Portfolio, 2017)
The timescale of isomerization in molecules involving ultrafast migration of constituent atoms is difficult to measure. Here the authors report that sub-100 fs isomerization time on acetylene dication in lower electronic states is not possible and point to misinterpretation of recent experimental results.